An Information Technology-Based Spiritual Emotional Freedom Technique (SEFT) Therapy Model on Sleep Quality and Premenstrual Syndrome Scores - Agustiarini, Anastasya; Santoso, Bedjo; Runjati, Runjati (Indonesian Journal of Global Health Research, 2024)
Premenstrual syndrome experienced by adolescent girls has many impacts, such as causing depression, which sometimes leads to suicidal thoughts or self-harm and others. The prevalence of premenstrual syndrome in Indonesia is 80.6% and in Semarang Polytechnic is 99%. By providing an information technology-based Spiritual Emotional Freedom Technique (SEFT) therapy model, it is expected to improve sleep quality and reduce premenstrual syndrome scores. This study used Research and Development (R&D) with a true experiment research design with a Pretest - Posttest Group Design. Non-probability sampling with purposive sampling technique was carried out to collect the sample. The results of the feasibility test with experts stated that the SEFT therapy model based on information technology deserved an average value of 88%. The information technology-based SEFT therapy model is effective to improve sleep quality and reducing premenstrual syndrome scores with a p-value of 0.00. The information technology-based SEFT therapy model is feasible to use as a medium to improve sleep quality and reduce premenstrual syndrome scores in adolescent girls.